2014
DOI: 10.1088/0960-1317/24/8/087001
|View full text |Cite
|
Sign up to set email alerts
|

A continuous flow micro filtration device for plasma/blood separation using submicron vertical pillar gap structures

Abstract: A continuous flow micro filtration device for plasma/blood separation using submicron vertical pillar gap structures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 17 publications
(34 reference statements)
1
22
0
2
Order By: Relevance
“…2 The principle behind that filtration technique was based on the size exclusion of cells, whereby only plasma was allowed to pass between the vertical pillars. The effectiveness of Kang et al's approach in separating blood plasma from whole blood was demonstrated experimentally; it was found to have a filtration efficiency of 99.9% and a plasma collection rate of 0.67 ll min À1 .…”
Section: A Microfiltration Based On Microchannel Obstructionmentioning
confidence: 99%
See 3 more Smart Citations
“…2 The principle behind that filtration technique was based on the size exclusion of cells, whereby only plasma was allowed to pass between the vertical pillars. The effectiveness of Kang et al's approach in separating blood plasma from whole blood was demonstrated experimentally; it was found to have a filtration efficiency of 99.9% and a plasma collection rate of 0.67 ll min À1 .…”
Section: A Microfiltration Based On Microchannel Obstructionmentioning
confidence: 99%
“…1 Compared to large-scale instruments, microfluidic devices require smaller samples and reagent volumes and provide better separation efficiency due to (1) a high surfaceto-volume ratio, (2) shorter analysis time, and (3) higher sensitivity. Microfluidic devices can even be integrated with other components toward a lab-on-a-chip (LOC).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these geometries, the size of the geometries determines the cells deformation [4]. Many literature studies use these structures (micropillars arrays and micro-weir filters), which create a cross-flow filtration to overcome some issues related with clogging and jamming [5,6]. However, for the best of the authors knowledge, the use of such structures was never used for separation and, at the same time, for measuring the deformation index of RBCs.…”
Section: Introductionmentioning
confidence: 99%